Analisis Peramalan Profitabilitas PT. Samudera Indonesia Tbk Menggunakan Metode Regresi Linear - Shiela, Fadia Jasmine Has; Hasanah, Indah Karimatul; Herlambang, Teguh; Ramadhan, Rizky; Hamdani, M. Yusuf; Nafa, Mulya (Zeta - Math Journal, 2024)
Logistics companies contribute significantly to economic growth and play an important role in global supply chains. Profitability is the main indicator of business success. The profit forecasting model helps managers improve financial performance efficiently and effectively. This research optimizes the financial performance of PT Samudera Indonesia Tbk by forecasting net profit using the linear regression method. Financial data from 2018 to 2023 was collected from the IDX website. Simulation analysis using Python shows that the independent variables in linear regression have a significant effect on the profitability of PT Samudera Indonesia Tbk. The regression coefficient shows the strength of the relationship between the independent and dependent variables. Linear regression models can predict profitability based on the variables considered. The aim of this research is so that PT Samudera Indonesia Tbk can carry out better financial planning and decisions based on accurate predictions. This research contributes to improving the operational efficiency and effectiveness of the company's business strategy, which has a positive impact on profitability and long-term growth. Overall, the application of the linear regression method in forecasting, with an RMSE value of 0.0645, is an effective tool for PT Samudera Indonesia Tbk to optimize financial performance amidst complex business competition.